The lost island eaudiobook A gideon crew novel. - Preston, Douglas (Gideon Crew, 2014)
Gideon Crew—brilliant scientist, master thief—is living on borrowed time. When his mysterious employer, Eli Glinn, gives him an eyebrow-raising mission, he has no reason to refuse. Gideon's task: steal a page from the priceless Book of Kells, now on display in New York City and protected by unbreakable security. Accomplishing the impossible, Gideon steals the parchment—only to learn that hidden beneath the gorgeously illuminated image is a treasure map dating back to the time of the ancient Greeks. As they ponder the strange map, they realize that the treasure it leads to is no ordinary fortune. It is something far more precious: an amazing discovery that could perhaps even save Gideon's life. Together with his new partner, Amy, Gideon follows a trail of cryptic clues to an unknown island in a remote corner of the Caribbean Sea. There, off the hostile and desolate Mosquito Coast, the pair realize the extraordinary treasure they are hunting conceals an even greater shock-a revelation so profound that it may benefit the entire human race . . . if Gideon and Amy can survive.